HIV infection among homosexual/bisexual males attending genitourinary clinics in Scotland. Issue 3 (June 1998) - Goldberg, D; Scott, G; Weir, M; Cameron, S; Peutherer, J; McMillan, A; Leadbetter, G; Scoular, A; Codere, G; Allardice, G
Abstract : BACKGROUND: Since 1991, unlinked anonymous HIV testing of homosexual/bisexual males attending genitourinary clinics in Edinburgh and Glasgow has been conducted and resulting prevalence data have been published annually. More detailed information which provides an understanding of what proportion of HIV infected men attending genitourinary clinics in central Scotland (i) remain undetected, (ii) acquire sexually transmitted infections following HIV diagnosis, and (iii) possibly become HIV infected either abroad or following sex with someone from abroad, is reported by the authors. METHODS: Unlinked anonymous HIV testing of syphilis serology specimens from homosexual/bisexual males attending genitourinary clinics during 1991-5. RESULTS: Of 3468 specimens tested, 165 (4.8%) were HIV positive. Thirty five per cent (57) of all HIV positive specimens were from men whose infection remained undetected following clinic attendance. Of the 80 attenders who knew themselves to be HIV positive before their clinic visit, 13 had clinical and/or laboratory evidence of a sexually transmitted infection. Men who had a sexual risk associated with America or who were American, had a 2.4-fold greater risk of being HIV infected than those with United Kingdom only connections. CONCLUSION: Increased efforts should be made to ensure that HIV infected men are diagnosed early after infection and do not engage in high risk sexual behaviour, and that all homosexual men are educated about the particular risks of acquiring HIV infection abroad. More effective interventions to prevent indigenous HIV transmissions need to be developed.